OS MANIFESTOS DE JOAQUIM: O espírito irreverente de 22 e as preocupações de 45 - L. de Lacerda Carollo, Cassiana (Revista Letras, 1972)
OS MANIFESTOS DE JOAQUIM: O espírito irreverente de 22 e as preocupações de 45